The Impact of the Global Citizenship Education Curriculum on the Quality of Learning Experiences of Graduate Students and Medical Assistants in Mazandaran Province - Hayati , Zahra; Rasoli, Seyedeh Esmat; Salimi , Ladan (Iranian Journal of Educational Sociology, 2026)
Purpose: The present study aimed to investigate the impact of a Global Citizenship Education Curriculum on the quality of learning experiences among graduate students and medical assistants in Mazandaran Province.Methodology: This study was applied in purpose and descriptive-correlational in design. The research population consisted of 1,665 graduate students and medical assistants in Mazandaran Province during the 2020–2021 academic year. Using Cochran’s formula, the sample size was determined to be 313 participants, who were selected through stratified random sampling. Data were collected using a researcher-developed Global Citizenship Education Curriculum questionnaire and the Learning Experiences Quality Questionnaire (Neumann, 1990). Data analysis was conducted using structural equation modeling in SPSS and PLS software.Findings: The findings indicated that the model assessing the impact of the Global Citizenship Education Curriculum on the quality of learning experiences among graduate students and medical assistants demonstrated good fit. The Global Citizenship Education Curriculum had a positive and significant effect on learning experience quality (P < .001). Furthermore, the three components of the Global Citizenship Education Curriculum—knowledge, attitude, and skills—had positive and significant effects on both the curriculum itself and all four components of learning experience quality, including library and computer resources, course content and value, learning flexibility, and the quality of formal and informal faculty–student relationships (P < .001).Conclusion: Considering the positive impact of the Global Citizenship Education Curriculum on the quality of learning experiences of graduate students and medical assistants, enhancing this curriculum can serve as an effective approach to improving learning experience quality.